The safety and efficacy of different methods for obtaining transbronchial lung cryobiopsy in diffuse lung diseases. (12th December 2017) - Dhooria, Sahajal; Mehta, Ravindra M.; Srinivasan, Arjun; Madan, Karan; Sehgal, Inderpaul Singh; Pattabhiraman, Vallandramam; Yadav, Pavan; Sivaramakrishnan, Mahadevan; Mohan, Anant; Bal, Amanjit; Garg, Mandeep; Agarwal, Ritesh
Abstract: Introduction: Most data on transbronchial lung cryobiopsy (TBLC) are from single centers, with little evidence on the outcome of different methods for performing TBLC. Objective: To report the diagnostic yield and safety of TBLC with different procedural techniques. Materials and Methods: Retrospective multicenter study of subjects who underwent TBLC for the diagnosis of diffuse parenchymal lung diseases (DPLDs). The procedure was performed using various methods: flexible or rigid bronchoscopy, with or without the use of fluoroscopy or occlusion balloon. Results: In total, 128 subjects (59% women) with a mean age of 48.9 years were included. The overall diagnostic yield of TBLC was 78.1%, with a definite diagnosis on multidisciplinary discussion made in 57 (44.5%) subjects. On a multivariate analysis, the diagnostic yield was associated with the number of biopsies taken {ajdusted odds ratio [AOR] [95% confidence interval (CI)], 2.17 [1.29‐3.67]}. The incidence of pneumothorax was lower in subjects who underwent TBLC with fluoroscopic guidance (5.9% vs 20.9%), [AOR (95% CI), 0.26 (0.07‐0.94)]. Moderate‐to‐severe bleeding occurred less frequently when an occlusion balloon was used [1.8% vs 35.7%; AOR (95% CI), 0.02 (0.001‐0.18)], after adjusting for age, use of fluoroscopy, number of biopsies obtained and number of lobes sampled. Four deaths occurred; 2 because of acute exacerbation of idiopathic pulmonary fibrosis. Conclusions: Transbronchial lung cryobiopsy was found to offer a reasonable yield in the diagnosis of DPLDs. The incidence of pneumothorax and moderate‐to‐severe bleeding was lower with the use of fluoroscopy and an occlusion balloon, respectively.